The potential of toothpaste containing Robusta coffee bean extract in reducing gingival inflammation and dental plaque formation - Peni Pujiastuti; Neira Najatus Sakinah; Yuliana Mahdiyah Da’at Arina; Melok Aris Wahyukundari; Depi Praharani; Desi Sandra Sari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: The prevention of gingivitis using chemicals containing antibiotics and chlorhexidine can disrupt the balance of the oral microbiota and have side effects in long-term use. A recent development in the prevention of gingivitis is the use of natural ingredients. Coffee is a natural ingredient that compounds several antibacterial and anti-inflammation properties. Purpose: The study aimed to determine the potential of toothpaste containing Robusta coffee bean extract in reducing gingival inflammation and inhibiting the formation of dental plaque. Methods: Twenty male Rattus norvegicus were divided into four groups, namely the control group and treatment groups (TG) TG25%, TG50%, and TG75%. All groups were fitted with ligature wire on the first left molar to accumulate dental plaque. After the fourth day, the ligature wire was removed, and the TG25%, TG50%, and TG75% groups were brushed once a day using toothpaste containing various concentrations of Robusta coffee extract, while the control group was brushed without using toothpaste. Plaque index, gingival index, and interleukin-1 (IL-1) expression were observed on the fifth day. The data was statistically tested using a one-way analysis of variance and post hoc least significant difference. Results: The statistical test showed that the TG75% group had the lowest value of plaque, gingival index, and IL-1 expression, while the control group had the highest (p < 0.05). Conclusion: Robusta coffee bean extract toothpaste has the potential to reduce gingival inflammation and dental plaque formation in a rat with gingivitis. The most effective concentration of Robusta coffee bean extract toothpaste in reducing gingival inflammation and dental plaque formation was 75%.